Exploring the Analytics Readiness Among Students in Kumasi Technical University, Ghana - Emmanuel Amos; Harry Barton Essel; George Kwame Fobiri; Akwasi Adomako Boakye; Yaw Boateng Ampadu (SAGE Open)
The increasing number of students in higher education has led to the formation of large class teaching and learning environments, which is a threat to quality education. The Department of Fashion Design and Textiles Studies of Kumasi Technical University is one such department that is facing this challenge. Computer-based technology has infiltrated many aspects of academic activities, yet there is little understanding of how it can be used to promote student engagement and educational data analysis in the classroom. This study explores the analytics readiness of students at the Department of Fashion Design and Textiles of Kumasi Technical University. The study used a mixed method of research and customized the JICS analytics readiness questionnaire as an instrument. With inspiration from the UTAUT model, a conceptual framework was designed to explore the factors (facilitation condition, social influence, and performance expectancy). With a sample size of 221 obtained with the purposive sampling technique, a descriptive and regression analysis were conducted to analyze data gathered from the respondents. The study revealed that existing structures, culture and policies in the institution are ready at its foundational state but will need an upgrade to sustain future educational data complexities. Also, the analysis revealed that facilitation conditions and performance expectancy have a significant effect on the student’s readiness to adopt LA. However, there was no significant relationship between social influence and students’ readiness. It is recommended that the needed resources for online learning should be provided coupled with appropriate policies to guide students in LA adoption.